18 best stories by Edgar Allan Poe - Poe, Edgar Allan, 1809-1849 (Dell, 1965)
A collection of eighteen classic short stories by nineteenth-century American poet and author, Edgar Allen Poe, including "The Black Cat," "The Tell-Tale Heart," and "The Cask of Amontillado."